PUBLIC EXTERNAL DEBT AND MACROECONOMIC STABILITY IN UZBEKISTAN: A REVIEW AND DESCRIPTIVE ANALYSIS - Elmirzayev Diyorbek Shoniyoz o’g’li (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  This  article  examines  the  evolution  of  public  external  debt  in  the Republic of Uzbekistan from 2015 to 2024, analyzing its pivotal role in the country's transition from an autarkic, state-led model to an open market economy. The study posits that while the nominal stock of public debt surged following the 2017 exchange rate  liberalization  and  subsequent  investment  boom,  the  debt-to-GDP  ratio  has stabilized within sustainable thresholds due to robust nominal GDP growth and prudent fiscal  management  (IMF,  2025).  Through  a  descriptive  analysis  of  the  evolving institutional framework, the research highlights the significance of the 2023 Law on State  Debt  and  the  maintenance  of  substantial  international  reserves  in  mitigating solvency  risks  (Ministry  of  Justice,  2023).  However,  the  analysis  also  identifies persistent structural vulnerabilities, specifically the high degree of foreign currency denomination and contingent liabilities arising from State-Owned Enterprises (SOEs). Ultimately, the research concludes that public debt served as a critical macroeconomic stabilizer  during  external  shocks,  positioning  Uzbekistan  for  a  phase  of  fiscal consolidation and deeper domestic market development.